2015
DOI: 10.1016/j.schres.2015.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Assessing suicidal ideation in individuals at clinical high risk for psychosis

Abstract: Background The majority of individuals with schizophrenia and other psychotic illnesses have had suicidal ideation at some point during the illness. However, little is known about the variation in level and intensity of suicidal ideation and symptoms in the attenuated stage of psychotic illness. Our aims were to assess prevalence of suicidal ideation in this at risk group, and to examine the severity and intensity of suicidal ideation, and their relation to symptoms. Methods Suicidal ideation was assessed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 26 publications
2
26
1
Order By: Relevance
“…Differently to our results, Gill et al. () observed that UHR people with suicidality showed greater severity of negative symptoms than those without suicidal behavior and that controlling for depressive symptoms did not substantially diminish the relationship. Together with these suggestions, our findings confirm the importance of differentiating between depressive and negative symptoms in UHR individuals, particularly for determining risk of suicide (other than conversion to psychosis) and in treatment planning.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Differently to our results, Gill et al. () observed that UHR people with suicidality showed greater severity of negative symptoms than those without suicidal behavior and that controlling for depressive symptoms did not substantially diminish the relationship. Together with these suggestions, our findings confirm the importance of differentiating between depressive and negative symptoms in UHR individuals, particularly for determining risk of suicide (other than conversion to psychosis) and in treatment planning.…”
Section: Discussioncontrasting
confidence: 99%
“…In this regard, positive correlations were found between BDI‐II item 9 score and three main psychopathological features: (1) depression severity (both in its cognitive and somatic‐affective components), (2) some specific items of the CAARMS related to Huber's basic symptoms (BS) (i.e., subjective emotional disturbance, subjective complaints of impaired autonomic functioning, and subjective tolerance to normal stress), and (3) CAARMS factor 1 (“Negative‐interpersonal dimension”). Differently from some previous studies (Bang et al., ; Gill et al., ; Niendam et al., ), this pattern coheres with findings of a previous study (Gill et al., ), who showed higher depression severity in UHR individuals with suicidal ideation in comparison with those without suicidal ideation. Moreover, in the current study, more severe levels of depressive symptoms correctly were the single most important psychopathological factor that predicted suicidal ideation in UHR+ adolescents (75% of correct dichotomized BDI‐II item 9 ascription in the logistic regression model).…”
Section: Discussionsupporting
confidence: 84%
“…The early stages of psychosis were also labeled as “ultra high risk (UHR),” “at risk mental state (ARMS),” and “clinical high risk (CHR).” It is well known that self-harm behaviors and suicidality are highly prevalent in the UHR population, with rates similar to those observed in samples diagnosed with psychotic disorders ( 20 ). In addition, about 50% of young people recognized to be CHR for psychosis have reported current suicidal thoughts ( 21 , 22 ). The prevalence of suicidal ideation among these samples is 42.9%, and there may also be less severe parasuicidal ideation ( 22 ).…”
Section: Subthreshold Psychotic Experiences and Suicide In Schizophrementioning
confidence: 99%
“…In addition, about 50% of young people recognized to be CHR for psychosis have reported current suicidal thoughts ( 21 , 22 ). The prevalence of suicidal ideation among these samples is 42.9%, and there may also be less severe parasuicidal ideation ( 22 ).…”
Section: Subthreshold Psychotic Experiences and Suicide In Schizophrementioning
confidence: 99%
See 1 more Smart Citation